Drug Susceptibility, Siderophore Production, and Genome Analysis of Staphylococcus aureus Clinical Isolates from a University Hospital in Chiang Mai, Thailand - Warinda Prommachote; Manu Deeudom; Pimpisid Koonyosying; Phronpawee Srichomphoo; Ratchanee Somnabut; Phadungkiat Khamnoi; Agostino Cilibrizzi; Yuvaraj Ravikumar; Somdet Srichairatanakool (Antibiotics)
Background/Objective:Staphylococcus aureus produces staphyloferrin A (Sfna) siderophores to sequester host iron during infection and rapid cell proliferation We examined drug susceptibility, siderophore production, and genome sequencing of clinical isolates of S. aureus. Methods: A total of 100 specimens, including pus, sputum, hemoculture, urine, tissue, fluid, and skin scrap specimens, were grown in iron-deprived Luria broth agar. The isolates were investigated for spectral signature using MALDI–TOF/MS, while antibiotic susceptibility and siderophore content were assessed using the chrome azurol S method. Whole genome and partial 16S rRNA DNA sequences were employed, and VITEK/MS revealed specific spectra. Results: Clindamycin, erythromycin, gentamicin, linezolid, moxifloxacin, oxacillin, trimethoprim/sulfamethoxazole, and vancomycin (100%) were the most common antibiotics to which the S. aureus isolates were susceptible. Sfna was not detectable in fluid and skin scrap isolates, which were encoded by sfnaB, sfnaD, and sfnaB/sfnaD genes. However, they were detectable in pus (73.8%), sputum (85.3%), hemoculture (50.0%), and urine (85.7%) isolates. The aureus subspecies, JKD6159, SA268, and MN8, were found to be 72.73% according to genome sequencing. Conclusion: most staphylococci in the isolates, including S. aureus JKD6159, SA268, and MN8, were sensitive to antibiotics and were detected by MALDI–TOF/MS, resulting in the production of Sfna encoded by sfna genes.